Proceedings -- The 27th International Symposium on Automation and Robotics in Construction 2010
DOI: 10.22260/isarc2010/0003
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Method of Construction Hoist Operating Plan for High Rise Buildings Considering Lifting Heights and Loads

Abstract: Lifting indicates vertical transfer of construction resources. In high-rise building, efficient plan and management on lifting of resources are essential because of enormous impact on schedule, and amount of resources and data. In particular, a hoist-one of main lifting equipment for workers and construction materials-may have direct influence on overall project schedule depending on its number, location and operation method. To ensure efficient construction, it is critical to have an optimal hoist operating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…For a more accurate estimation of the hoisting time, this study adopted calculation method considering acceleration and deceleration, suggested by Cho et al [12]. Also, we utilized the acceleration and deceleration time of single-cage lift which was provided by Cho et al [13].…”
Section: Calculation Methods Of Hoisting Timementioning
confidence: 99%
“…For a more accurate estimation of the hoisting time, this study adopted calculation method considering acceleration and deceleration, suggested by Cho et al [12]. Also, we utilized the acceleration and deceleration time of single-cage lift which was provided by Cho et al [13].…”
Section: Calculation Methods Of Hoisting Timementioning
confidence: 99%
“…Sin et al [19,20] proposed an unmanned smart lifting system and devised an optimized operation algorithm for twin or multi-cage lifts, which can reduce work hours and traffic queues. Cho et al [21] provided a simulation method of construction hoists to calculate the lifting cycle time according to lifting heights and loads, and to generate an optimal hoist operating plan. They also developed an optimal algorithm [22] for path planning of the multi-lifting operation in super-tall buildings.…”
Section: Automated Lifting Systemsmentioning
confidence: 99%
“…Given these circumstances, this study conducts a simulation on construction hoist operation, explores how to improve movement of materials and labors in super high-rise construction by developing optimized operation algorithm. The simulation results are assessed based on the cycle time of daily unit work processes according to lifting cycle time calculation (Cho, 2010).…”
Section: Introductionmentioning
confidence: 99%